PENINGKATAN KOMPETENSI KEWIRAUSAHAAN DAN KINERJA USAHA PENJUAL PAKAIAN JADI PADA USAHA KECIL MENENGAH (UKM) DI KABUPATEN SIDRAP - Muhammad Yunus (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2020)
This study aims to determine the factors that influence (i) individual characteristics of entrepreneurial competencies, (ii)human resources towards entrepreneurship competencies, (iii) entrepreneurial orientation towards entrepreneurshipcompetencies (iv) environment towards entrepreneurship competencies and (v) entrepreneurial competencies towardsbusiness performance. This research belongs to the category of explanatory research (explanatory research). The studywas conducted on small and medium businesses spread across Sidrap Regency. The research population is small andmedium enterprises in the economic sector of textile entrepreneurs and apparel entrepreneurs based on 2013-2014 data.The number of SMEs experienced a reduction of 1.85% and 5.36% respectively in 2013 and 2014. The samplingtechnique uses a sample technique (stratified random sampling), (stratified random sampling), i.e. taking stratifiedrandom samples (groups) with the number a sample of 300 entrepreneurs. In this study, contextual factors, as independent variables, are tested as potential predictors of the dimensions of each predictor for the components of entrepreneurial performance. The contextual factor is business performance (Y1) as the dependent variable and entrepreneurial competence as an intervening variable (Y2). Conceptual factors as independent variables are (X) consisting of individual characteristics (X1), human resources (X2), entrepreneurial orientation (X3) and environmental factors (X4). The results of this study indicate that the variables of individual characteristics, human resources, entrepreneurial orientation, and the environment together with each of their dimensions indicate that there is a significant influence between exogeng variables and endogenous variables simultaneously and partially on entrepreneurial competence and on business performance.Keyword - Personality, Environment, Entrepreneurship Competence and Business Performance